Immersive Two-Channel Recordings Based on Personalized BRIRs and Their Applications in Industry - Kaja Kosmenda; Witold Mickiewicz (Applied Sciences)
The realm of immersive sound technologies in modern industries is evolving every day. Two-channel recordings using personalized HRIRs or BRIRs, which are tailored to the unique anatomical features of individual listeners, significantly enhance the spatial accuracy and naturalness of sound, providing a highly immersive auditory experience. This paper discusses the importance of immersive sound and the externalization effect in recreating the acoustic environment. The paper also presents techniques for obtaining two-channel immersive renderings in a few different ways. The main focus is the integration of immersive audio in new technologies in the wide-ranging audio industry, from telecommunication, through applications for musicians, virtual reality scenarios, and hearing devices. In summary, this paper highlights the huge potential of personalized BRIRs in creating immersive two-channel recordings, offering substantial benefits across various industries by improving the realism and effectiveness of each auditory experience on its own.